PENGARUH KEPEMIMPINAN, PENDIDIKAN DAN PELATIHAN TERHADAP KINERJA PEGAWAI DI BALAI DESA WILAYAH TRIMULIA LAMPUNG BARAT - Rini Loliyani; Rina Loliyana; Nety Kumalasari (Jurnal Manajemen dan Bisnis (JMB), 2022)
ABSTRACTThis study aims to determine the effect of partial and simultaneous leadership variables, education and training on the performance of employees in the Central Region trimulia lampung barat. Populasi in this study are employees in the Central Region trimulia lampung barat with a sample of 46 respondents. Sampling technique using Saturated sampling method. Data collection techniques used were questionnaires, documentation and interviews. Instrument test instrument of this study is the test of validity and reliability test, while for testing the hypothesis using f test and t test. Researchers also use multiple linear regression analysis to analyze data and reinforced by the classical assumption test that is test of normalistas, multikolinearitas, heterokedastisitas and autokorelasi. The result of data analysis shows that leadership, education and training variables have a significant positive effect both simultaneously and partially on the performance of employees in River trimulia lampung barat. Keywords: leadership, Education, Training and Performance